Preparation method of MOF-based lithium-sulfur battery diaphragm material

By integrating a frame from metal to Cr-MOF in the lithium sulfur battery separator, bimetal MOF-based separator material is prepared, which solves the problem of reduced battery cycle life caused by lithium polysulfide shuttle effect, and achieves higher utilization rate of active substances and battery cycle performance.

CN119662127APending Publication Date: 2025-03-21SHANGHAI ELECTRIC GOTION NEW ENERGY TECH (NANTONG) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411943884.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The shuttle effect of lithium polysulfide in lithium sulfur batteries leads to an increase in the viscosity of the electrolyte, reducing ionic conductivity, and thus reducing the battery cycle life. The existing cathode materials have poor electrical conductivity and limited adsorption and conversion capabilities, which cannot effectively solve this problem.

Method used

The metal was integrated into the frame of Cr-MOF by solvent thermal method to prepare a bimetallic MOF-based lithium-sulfur battery separator material. The material has an ordered microporous structure, the average pore size is smaller than the diameter of lithium polysulfide, and introduces metal active sites, which can adsorb and catalytically convert lithium polysulfide.

Benefits of technology

Significantly reduce the shuttle effect of lithium polysulfide, improve the utilization rate of active materials, and enhance the circulation performance and capacity retention rate of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of lithium-sulfur batteries, in particular to a preparation method of an MOF (Metal Organic Framework)-based lithium-sulfur battery diaphragm material, which starts from the aspect of diaphragm modification of a lithium-sulfur battery, and integrates another metal into a Cr-MOF framework as a diaphragm coating material of the lithium-sulfur battery through a simple solvothermal method. A channel of a three-dimensional structure is composed of ordered micropores, the average size of the channel is smaller than the diameter of lithium polysulfide, and catalytic conversion of lithium polysulfide adsorbed in a lithium-sulfur battery can be achieved through multiple introduced metal active sites while the shuttle problem of lithium polysulfide is solved, so that accumulation of lithium polysulfide is reduced, and the utilization rate of an active material is increased; according to the MOF-based diaphragm disclosed by the invention, firstly, the shuttle effect of lithium polysulfide can be obviously reduced;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous material preparation technology, and specifically to a method for preparing a MOF-based lithium-sulfur battery diaphragm material. Background Art

[0002] Currently, lithium-ion batteries dominate the energy storage and power market, and their applications are very wide, ranging from portable electronic products of various sizes to electric vehicles. Although lithium-ion batteries have a large market share, their performance is subject to some technical limitations, such as limited theoretical capacity. Therefore, people are increasingly studying other battery systems.

[0003] Among them, lithium-sulfur batteries are considered to be one of the most promising energy storage technologies due to their high theoretical capacity (1675 mAh / g) and energy density (2500 Wh / kg), as well as their considerable cost-effectiveness and environmental friendliness. The reaction mechanism of lithium-sulfur batteries is different from the ion extraction and insertion mechanism of lithium-ion batteries, but an electrochemical mechanism. During the charging and discharging process, the sulfur in the positive electrode undergoes a multi-electron redox reaction to form an intermediate reaction product, which is commonly known as soluble lithium polysulfide, and is further reduced to insoluble Li2S. However, the dissolution and migration of lithium polysulfide between electrodes (i.e., the shuttle effect) will lead to an increase in the viscosity of the electrolyte, reduce the ionic conductivity, and further lead to a decrease in the battery cycle life. In order to solve this problem as much as possible, people have widely studied various materials, such as preparing sulfur-based composite positive electrode materials by combining active sulfur with activated carbon, metal carbides, sulfides and oxides with good conductivity and specific structures.

[0004] However, most cathode materials have problems such as poor conductivity and limited adsorption and conversion capabilities for lithium polysulfide. The shuttling of lithium polysulfide is carried out through the non-selective pores in the separator. Therefore, one of the most direct ways to limit the passage of lithium polysulfide through the separator is to introduce the selective function of lithium polysulfide into the separator. If the separator also has the function of adsorption and catalytic conversion of lithium polysulfide, the above situation can be further improved. In recent years, metal organic framework (MOFs) materials have been considered as a promising separator modification component due to their high specific surface area, highly interconnected and ordered pores, rich cavity structure, and inorganic-organic hybrid properties.

[0005] Currently, researchers have explored various MOFs materials as coating materials for lithium-sulfur battery separators, but MOFs have poor conductivity and structural stability under battery operating conditions, and many MOFs are easily degraded or lose function at high temperatures or in electrolytes, so they are not common in the new generation of battery separators.

[0006] In order to improve the utilization rate of active material sulfur and limit the dissolution of lithium polysulfide and the problem of poor battery cycle performance, researchers generally start from the two aspects of electrolyte and positive electrode materials, and involve less in the diaphragm. At present, MOFs materials are explored as coating materials for lithium-sulfur battery diaphragms, but they can only solve the shuttling problem of lithium polysulfide, which is not enough to achieve a significant improvement in the performance of lithium-sulfur batteries. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing a MOF-based lithium-sulfur battery separator material to solve the problems raised in the above background technology.

[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing a MOF-based lithium-sulfur battery separator material, comprising the following steps: Step 1: Dissolve an appropriate amount of Cr(NO3)3·9H2O, another metal nitrate and 2-aminoterephthalic acid in DMF (dimethylformamide), then mix the above three solutions with a certain amount of DMF and acetic acid and transfer them to a hydrothermal reactor. After a period of reaction at a certain temperature, cool the product and take it out and wash it with acetone and ethanol several times to remove impurities. Finally, dry the obtained bimetallic MOF material at a certain temperature overnight. Step 2: Weigh an appropriate amount of the MOF material, PVDF and Super-P in step 1 and mix them in NMP in a certain proportion, stir them evenly to obtain a MOF-based diaphragm coating slurry, and then put it into a sealed container for ball milling for a period of time; Step 3: Weigh a certain amount of the slurry in step 2, and use a simple coating machine to evenly coat it on the PP diaphragm. Finally, after drying at a certain temperature for a period of time, a bimetallic MOF-based modified lithium-sulfur battery diaphragm material (MIL-101(M / Cr)-NH2) is obtained.

[0009] Preferably, in step 1, the dosage ratio of the three solids Cr(NO3)3·9H2O, metal nitrate, 2-aminoterephthalic acid and DMF is 1mmol:1mmol:1mmol:(1-10)ml; the volume ratio of the three solutions to DMF and acetic acid is (1-5):(1-5):(1-15):(1-10):(1-10).

[0010] Preferably, the metal nitrate in step 1 is one of the nitrates of transition metal elements.

[0011] Preferably, in step 1, the reaction temperature is 100-160° C., and the reaction time is 8-24 h.

[0012] Preferably, the drying temperature of the sample in step 1 is 40-80°C, and the drying time is 10-24 h.

[0013] Preferably, the mass fraction ratio of the MOF material, PVDF and Super-P in step 2 is (50-80): (10-25): (10-25).

[0014] Preferably, the ball milling time in step 2 is 0.5 to 2 h.

[0015] Preferably, the thickness of the slurry coating in step 3 is 5-10 μm.

[0016] Preferably, the drying temperature in step 3 is 40-80°C; and the drying time is 10-24 h.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention starts with the modification of the diaphragm of the lithium-sulfur battery, and integrates another metal into the framework of Cr-MOF as the diaphragm coating material of the lithium-sulfur battery through a simple solvothermal method. The channels of the 3D structure are composed of ordered micropores, and the average size is smaller than the diameter of lithium polysulfide. While solving the problem of lithium polysulfide shuttling, the introduced metal active sites can also realize the catalytic conversion of lithium polysulfide adsorbed in the lithium-sulfur battery, thereby reducing the accumulation of lithium polysulfide and improving the utilization rate of active materials. The MOF-based diaphragm of the present invention can firstly significantly reduce the shuttling effect of lithium polysulfide; Compared with commercial polyolefin separators and conventional single-metal MOFs, the bimetallic MOF-based modified separator coating material in the present invention not only provides uniformly sized nanochannels for the effective adsorption of lithium polysulfide and the transmission of lithium ions, but also provides metal active sites for the electrocatalytic conversion of lithium polysulfide, thereby effectively improving the utilization rate of active materials and the cycle performance of lithium-sulfur batteries. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] The present invention provides a technical solution: a method for preparing a MOF-based lithium-sulfur battery diaphragm material, comprising the following steps: Step 1, dissolve an appropriate amount of Cr(NO3)3·9H2O, another metal nitrate and 2-aminoterephthalic acid in DMF respectively, then mix the above three solutions with a certain amount of DMF and acetic acid and transfer them to a hydrothermal reactor. After reacting at a certain temperature for a period of time, the product is taken out after cooling and washed with acetone and ethanol several times to remove impurities. Finally, the obtained bimetallic MOF material is dried overnight at a certain temperature.

[0020] Specifically, the dosage ratio of the three solids Cr(NO3)3·9H2O, metal nitrate, 2-aminoterephthalic acid and DMF is 1mmol:1mmol:1mmol:(1~10)ml, preferably 1mmol:1mmol:1mmol:(1~5)ml; the volume ratio of the three solutions to DMF and acetic acid is (1~5):(1~5):(1~15):(1~10):(1~10), preferably (1~5):(1~5):(5~10):(5~8):(5~8); the metal nitrate is one of the nitrates of transition metal elements, preferably one of iron nitrate, cobalt nitrate, nickel nitrate and copper nitrate; the reaction temperature is 100~160℃, preferably 120~150℃, and the reaction time is 8~24h, preferably 12~24h; the drying temperature of the sample is 40~80℃, preferably 60~80℃, and the drying time is 10~24 h, preferably 12 h.

[0021] Step 2, weigh an appropriate amount of the MOF material, PVDF and Super-P in step 1, mix them in a certain proportion in NMP, stir them evenly to obtain a MOF-based diaphragm coating slurry, and then put it into a sealed container for ball milling for a period of time.

[0022] Specifically, the mass fraction ratio of the MOF material, PVDF and Super-P is (50-80): (10-25): (10-25), preferably (60-80): (10-20): (10-20); the ball milling time is 0.5~2 h.

[0023] Step 3, weigh a certain amount of the slurry in step 2, use a simple coating machine to evenly coat it on the PP diaphragm, and finally dry it at a certain temperature for a period of time to obtain a bimetallic MOF-based modified lithium-sulfur battery diaphragm material.

[0024] Specifically, the thickness of the slurry coating is 5-10 μm; the drying temperature is 40-80° C., preferably 40-60° C.; and the drying time is 10-24 h, preferably 12 h. Example

[0025] Weigh equimolar masses of Cr(NO3)3·9H2O and Fe(NO3)3·9H2O and 2-aminoterephthalic acid and dissolve them in DMF at a ratio of 1mmol:5 ml, then mix the three solutions with DMF and acetic acid at a volume ratio of 5:5:10:8:8 and transfer them to a hydrothermal reactor, react at 150°C for 12 h, take out the product after cooling and wash it with acetone and ethanol several times to remove impurities, and dry the obtained bimetallic MOF material at 80°C for 12 h. Then mix the above MOF material with PVDF and Super-P in NMP at a mass fraction ratio of 70:20:10, stir evenly to obtain a MOF-based diaphragm coating slurry, and then put it into a sealed container for 1 hour of ball milling. Finally, a certain amount of slurry was weighed and evenly coated on a commercial PP separator using a simple coating machine. The coating thickness was about 5 μm. After drying at 60 °C for 12 h, a bimetallic MOF-based modified lithium-sulfur battery separator material (MIL-101(Fe / Cr)-NH2) was obtained.

[0026] Comparative Example 1 Weigh equimolar masses of Cr(NO3)3·9H2O and 2-aminoterephthalic acid and dissolve them in DMF at a ratio of 1mmol:5ml, then mix the two solutions with DMF and acetic acid at a volume ratio of 5:10:8:8 and transfer them to a hydrothermal reactor, react at 150℃ for 12h, take out the product after cooling and wash it with acetone and ethanol several times to remove impurities, and dry the obtained Cr-MOF material at 80℃ for 12h. Then mix the above MOF material with PVDF and Super-P in NMP at a mass fraction ratio of 70:20:10, stir evenly to obtain MOF-based membrane coating slurry, and then put it into a sealed container for 1h of ball milling. Finally, a certain amount of slurry was weighed and evenly coated on a commercial PP separator using a simple coating machine. The coating thickness was about 5 μm. After drying at 60 °C for 12 h, a Cr-MOF-based modified lithium-sulfur battery separator material (MIL-101(Cr)-NH2) was obtained.

[0027] Comparative Example 2 The diaphragm material used in this comparative example is a 12 μm PP diaphragm commonly used on the market.

[0028] The diaphragm materials described in Example 1, Comparative Example 1 and Comparative Example 2 were respectively assembled into lithium-sulfur batteries and subjected to cycle testing, the steps being as follows: The sulfur positive electrode, MOF-modified diaphragm, lithium metal negative electrode and electrolyte were assembled into button batteries in sequence in a glove box with an argon atmosphere. The assembled batteries were then placed on a battery testing system for charge and discharge tests. The test voltage range was 1.7-2.8 V, and the cycle test rate was 0.33C (0.1C for the first two cycles).

[0029] The following table shows the electrochemical performance results of lithium-sulfur batteries assembled with the diaphragm materials in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0030] Sample name First discharge capacity (mAh / g) Capacity retention rate (%, 0.33C, 100cls) Example 1 1045.6 87.8 Comparative Example 1 855.3 80.5 Comparative Example 2 600.8 47.2 Table 1 Electrochemical performance results of lithium-sulfur batteries assembled from diaphragm materials in Example 1, Comparative Example 1, and Comparative Example 2 It can be seen from Table 1 that after 100 charge and discharge cycles, the capacity retention rate of the lithium-sulfur battery of Example 1 is 87.8%, the capacity retention rate of Comparative Example 1 is 80.5%, and the capacity retention rate of Comparative Example 2 is 47.2%.

[0031] It can be seen that the lithium-sulfur battery assembled with the bimetallic MOF-based modified lithium-sulfur battery separator material in Example 1 has a high discharge capacity retention rate and good cycle performance.

[0032] It is obvious to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive in all respects, and the scope of the invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims be included in the invention.

[0033] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a MOF-based lithium-sulfur battery diaphragm material, characterized in that: The following steps are involved: Step 1: Dissolve an appropriate amount of Cr(NO3)3·9H2O, another metal nitrate and 2-aminoterephthalic acid in DMF (dimethylformamide), then mix the above three solutions with a certain amount of DMF and acetic acid and transfer them to a hydrothermal reactor. After a period of reaction at a certain temperature, cool the product and take it out and wash it with acetone and ethanol several times to remove impurities. Finally, dry the obtained bimetallic MOF material at a certain temperature overnight. Step 2: Weigh an appropriate amount of the MOF material, PVDF and Super-P in step 1 and mix them in NMP in a certain proportion, stir them evenly to obtain a MOF-based diaphragm coating slurry, and then put it into a sealed container for ball milling for a period of time; Step 3: Weigh a certain amount of the slurry in step 2, and use a simple coating machine to evenly coat it on the PP diaphragm. Finally, after drying at a certain temperature for a period of time, a bimetallic MOF-based modified lithium-sulfur battery diaphragm material (MIL-101(M / Cr)-NH2) is obtained.

2. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: In step 1, the dosage ratio of Cr(NO3)3·9H2O, metal nitrate, 2-aminoterephthalic acid and DMF is 1mmol:1mmol:1mmol:(1-10)ml; the volume ratio of the three solutions to DMF and acetic acid is (1-5):(1-5):(1-15):(1-10):(1-10).

3. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: The metal nitrate in step 1 is one of the nitrates of transition metal elements.

4. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: In step 1, the reaction temperature is 100-160°C and the reaction time is 8-24 h.

5. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: In step 1, the drying temperature of the sample is 40~80 ℃, and the drying time is 10~24 h.

6. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: The mass fraction ratio of the MOF material, PVDF and Super-P in step 2 is (50-80): (10-25): (10-25).

7. The method for preparing the lightweight and low thermal conductive lutetium silicate aerogel according to claim 1, characterized in that: The ball milling time in step 2 is 0.5~2 h.

8. The method for preparing the lightweight and low thermal conductive lutetium silicate aerogel according to claim 1, characterized in that: The thickness of the slurry coating in step 3 is 5-10 μm.

9. The method for preparing the lightweight and low thermal conductivity lutetium silicate aerogel according to claim 1, characterized in that: The drying temperature in step 3 is 40-80°C; the drying time is 10-24 hours.

Citation Information

Cited By

  • High-capacity and high-energy-density lithium / carbon fluoride battery and preparation method thereof

    CN120895672A